#### Answer

17

#### Work Step by Step

$(f+g)(x)=f(x)+g(x)$
$(f+g)(x)=f(x)+g(x)=x^2-3x+8-2x-5=x^2-5x+3$
Plug in $x=-2$ into $(f+g)(x)$: $(f+g)(-2)=(-2)^2-5(-2)+3=4+10+3=17$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

17

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.